Obsession - Woods, Stuart; Battles, Brett (Woods, Stuart. Teddy Fay novel, 2023)
"While filming on location in scenic Santa Barbara, California, Peter Barrington and Ben Bacchetti look to expand Centurion Studios by making a deal with a Croatian tech billionaire's. But when the magnate's wife is kidnapped, Teddy Fay is brought in to assess the threat and recover the young woman. As Teddy unravels the threads of her disappearance, he quickly comes to find an old vendetta that seethes at the center, one that puts them all at risk. And danger is lurking even nearer to home as an obsessive fan with perilous intentions who weasels his way onto the film set. It's only Teddy who can stop him frmo getting too close for comfort" --